(f-g)(X) = f(X)-g(X) = 5x^3-2-x-1= 5x^3-x-3
Answer:
[see below]
Step-by-step explanation:
Randy first won 12 points on Monday. He earned as twice as many on Tuesday.
12 * 2 = 24
Randy scored 24 points Tuesday.
Randy earned 3 more points than Tuesday's points the next day.
24 + 3 = 27
Randy earned 27 points Wednesday.
12 + 24 + 27 = 63
Randy should earn a total of 63 points for the 3 days.
Hope this helps.
Funciton form is f(x)=something
basicallly know that f(x) is the output or y
just solve for y
-3x-6y=0
add 3x to both sides
-6y=3x
divide both sides by -6
y=-1/2x
f(x)=(-1/2)x
To solve the given problem
We can consider,
30% are girls of 30 people
70% are boys in 30 people
In order to get the number, we just multiply the total number
of people with the percentage of the designated target populace.
<span><span>1. </span>30 x 0.3 =
9 girls</span>
<span><span>
2. </span>30 x 0.7 =
21 boys</span>
<span><span>
3. </span>21 boys + 9
girls = 30 people</span>
Hence, there are 21 boys.